2019
DOI: 10.3390/cells8091025
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Adult Endogenous Neural Stem/Progenitor Cells in the Spinal Cord to Contribute to Remyelination in Experimental Autoimmune Encephalomyelitis

Abstract: Demyelination and remyelination play pivotal roles in the pathological process of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), a well-established animal model of MS. Although increasing evidence shows that various stimuli can promote the activation/induction of endogenous neural stem/progenitor cells (NSPCs) in the central nervous system, the potential contributions of these cells to remyelination following inflammatory injury remain to be fully investigated. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 70 publications
3
30
0
Order By: Relevance
“…Neurosphere-like cell clusters were subjected to reverse transcription polymerase chain reaction (RT-PCR) 21 d after incubation (see below). Clusters were differentiated on poly- l -lysine-coated (0.05%) glass coverslips for 7 d in neurobasal medium (Invitrogen) containing bFGF, B-27 supplement (Invitrogen), and 2% fetal bovine serum as previously described [ 20 ]. The differentiated cell clusters were subjected to RT-PCR and immunohistochemistry using antibodies against Tuj1 (1:1000; mouse; Stemcell Technologies, Vancouver, BC, Canada), MAP-2 (1:1000, rabbit, Millipore), glial fibrillary acidic protein (GFAP) (1:1000, rabbit, Abcam), and myelin basic protein (MBP) (1:100, R&D systems), followed by Alexa Fluor 488- or 555-conjugated secondary antibodies (1:500; Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurosphere-like cell clusters were subjected to reverse transcription polymerase chain reaction (RT-PCR) 21 d after incubation (see below). Clusters were differentiated on poly- l -lysine-coated (0.05%) glass coverslips for 7 d in neurobasal medium (Invitrogen) containing bFGF, B-27 supplement (Invitrogen), and 2% fetal bovine serum as previously described [ 20 ]. The differentiated cell clusters were subjected to RT-PCR and immunohistochemistry using antibodies against Tuj1 (1:1000; mouse; Stemcell Technologies, Vancouver, BC, Canada), MAP-2 (1:1000, rabbit, Millipore), glial fibrillary acidic protein (GFAP) (1:1000, rabbit, Abcam), and myelin basic protein (MBP) (1:100, R&D systems), followed by Alexa Fluor 488- or 555-conjugated secondary antibodies (1:500; Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using an RNeasy Micro Kit (Qiagen, Hilden, Germany) as previously described [ 12 , 20 , 21 , 22 ]. In brief, total RNA was extracted from the differentiated cell clusters obtained after 90-min t-MCAO and p-MCAO.…”
Section: Methodsmentioning
confidence: 99%
“…There is also increasing evidence showing that various types of stem cell populations such as neural stem/progenitor cells (NSPCs) reside in the central nervous system [ 86 , 87 ]. The precise origins and traits of stem cells that contribute to neural repair remain unclear; however, a growing body of evidence indicates that brain pericytes can behave as NSPC-like cells under pathological conditions such as those observed after ischemic stroke [ 21 , 22 , 62 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…However, increasing evidence shows that remyelination occurs in the MS/EAE [57][58][59][60]. In addition, recent studies showed that activated neural stem/progenitor cells around region sites contribute to remyelination [61,62]. Promoting remyelination, therefore, provides an additional line of defense against the axonal damage that follows the loss of myelin.…”
Section: Nanotechnology and Msmentioning
confidence: 99%